Idea Generation Through Hackathon Event in Emergencies and Disasters, with Emphasis on Managing Flash Flood Disaster. (18th June 2022) - Monsef, Sanaz; Haghjooy Javanmard, Shaghayegh; Amini-Rarani, Mostafa; Yarmohammadian, Mohammad H.; Yazdi, Youseph; Haghshenas, Abbas
Abstract: Objective: This study was intended to demonstrate the applicability of the hackathon in idea generation for managing emergencies and disasters with a particular focus on flash floods. Methods: A 4-day hackathon event was held, having 60 students, 9 mentors and 6 judges gathered to explore different ideas, and to solve problems of Iran flooding from mid-March to April, 2019. Of these, 10 teams with 6 students were accordingly formed to brainstorm and discuss the idea, while 9 mentors offered advice and guided them to manage their ideas. Then, all teams focused on designing their business models. Finally, the hackathon teams finalized their lean canvas and presented their ideas to the judging panel and the other participants. Results: A total of 10 ideas were presented, and based on the knowledge and experience of the judges, 3 ideas that were more practical and useful were selected. Conclusions: As participants in a hackathon identify and present real-world problems, while ensuring that the prototype solutions address the end-user's needs, it could be used to drive innovation, generate ideas, promote change in emergencies and disasters, and can increase our preparedness for future events. It helps us to develop tools and applications to better respond to these events.